2012
DOI: 10.1007/s10157-012-0637-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of lymphatic vasculature and morphological characterization in rat kidney

Abstract: During nephrogenesis, lymphatic vessels extend from the renal hilus into the renal cortex along the renal blood vasculature. Podoplanin, prox-1, Ki-67, type IV collagen, and αSMA immunostaining can detect lymphatic vessels during lymphangiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…7A-B). In agreement with previous studies (Tanabe et al, 2012), renal Nrp2 þ lymphatic vessels extend along the segmental vasculature from the renal pelvis (Fig. 7C).…”
Section: Developmental Dynamicssupporting
confidence: 93%
“…7A-B). In agreement with previous studies (Tanabe et al, 2012), renal Nrp2 þ lymphatic vessels extend along the segmental vasculature from the renal pelvis (Fig. 7C).…”
Section: Developmental Dynamicssupporting
confidence: 93%
“…Later studies taking advantage of more specific markers such as podoplanin, LYVE-1, Prox-1 and VEGFR-3 confirmed the previous findings on the distribution of renal lymphatics ( Refs 19,20,21,22). D2-40, a monoclonal antibody which recognises human podoplanin, validated the pattern of human renal LVs that had been uncovered by previous investigations (Refs 23,24,25).…”
Section: Lvs In Kidneysupporting
confidence: 80%
“…There are no LVs at that point around the arcuate arteries and in the cortical area. However, one day after birth, several small LVs can be observed around 20,21). Two lymphatic systems have been observed in human kidneys.…”
Section: Lvs In Kidneymentioning
confidence: 96%
“…However, Tammela et al (49) observed VEGFR3 in tip cells of endothelial sprouts mediating sprouting of blood vessels. Medullary lymphatic vessels have not been detected during kidney development (50), and consistent with this, we observed no expression of VEGFR3 in total renal medulla or vasa recta during vascular bundle expansion. VEGFR3 inhibition therefore seems an unlikely contributor to the observed effect on microvessel expansion and impaired VEGFR2 is believed to be the main contributor.…”
supporting
confidence: 90%